Von Willebrand factor and alkaline phosphatase predict re-transplantation-free survival after the first liver transplantation - Wannhoff, Andreas; Rauber, Conrad; Friedrich, Kilian; Rupp, Christian; Stremmel, Wolfgang; Weiss, Karl Heinz; Schemmer, Peter; Gotthardt, Daniel (United european gastroenterology journal, 2017)
BackgroundAfter liver transplantation (LT), there are liver-related, infectious and cardiovascular complications that contribute to reduced graft survival. These conditions are associated with an increase in the Von Willebrand factor antigen (VWF-Ag), which was previously correlated with survival in cirrhotic patients.ObjectiveEvaluate VWF-Ag as a predictive marker of re-transplantation-free survival in patients after LT.MethodsWe measured VWF-Ag in patients after first LT and then followed them prospectively with regard to the primary endpoint, namely re-transplantation-free survival.ResultsThere were 6 out of 80 patients who died or received re-LT during follow-up. In these patients, the median VWF-Ag was 510.6%, which was significantly higher (p?=?0.001) than in the patients who were alive at the end of follow-up (with a median VWF-Ag?=?186.8%). At a cut-off of 286.8%, VWF-Ag was significantly correlated with re-transplantation-free survival (p?